TEST FOR DETERMINATION OF CORROSION OF METALS IN DIFFERENT ENVIRONMENTS LIMA AND CALLAO - Pizarro-Cabrera, R. (1999)
We have studied the effect of corrosion on two samples of steel alloys widely used in Lima and Callao. Low alloy steel grade API-SLX-42 manufactured by Sider Peru SA and galvanized steel manufactured by Ferrum SA Peru are exposed to different environments such as local air urban, industrial and marine. As a result it was found that the galvanized steel is more corrosion resistant low alloy steel. The author proposes mathematical models that describe in each case the behavior of metals under! Studied as environmental conditions.